Algiers as a Paradigmatic Mediterranean City: El Houma as a Measure of Urban Life. Issue 2 (3rd April 2022) - Khemri, Mohamed Yazid; Melis, Alessandro
Abstract: With cities accommodating a growing share of the global population, they are exposed to rapid rates of globalisation and urbanisation that present a significant challenge to their capacity to satisfy people's needs and aspirations and promote urban life. A thorough understanding of how urban forms can promote or hinder urban life has never been more pertinent. This paper contributes to filling this gap by analysing urban form features and synthesising theoretical and empirical evidence on how the physical design of neighbourhoods promotes or hinders urban life. This paper takes Algiers as a paradigmatic case study to explore the relationship between urban form and urban life in the Mediterranean region. It argues that urban form is a factor in facilitating social activities. The paper will base its investigation on the concept of El Houma, which can provide an effective instrument to measure urban life. El Houma is a term used in Algeria to describe a neighbourhood or an urban area characterised by a strong degree of social sustainability, based on the local socio-cultural life of residents manifested in the social use of urban space. In this respect, the paper will review features of three urban planning movements: medieval urbanism, the 19th-century bourgeois city and modernism. The research will draw on urban morphological analysis and techniques of activity mapping to investigate the relationship between urban forms and urban life, illustrated in El Houma, in three different neighbourhoods that represent the three urban planning strands. The paper concludes that the intensity of El Houma is high in the medieval and 19th-century neighbourhoods due to features of urban forms that foster social use of space, and lower in modernist neighbourhoods due to the lack of appropriate spaces for social interaction and forming social relations between residents. Findings indicate that urban form has a major influence on social use of space, urban life and thus El Houma.